A survey in natural olive resources exposed to high inoculum pressure indicates the presence of traits of resistance to Xylella fastidiosa in Leccino offspring - La Notte, Pierfederico; Saponari, Maria; Mousavi, Soraya; Mariotti, Roberto; Abou Kubaa, Raied; Nikbakht, Roya; Melcarne, Giovanni; Specchia, Francesco; Altamura, Giuseppe; Ligorio, Angela; Boscia, Donato; Surano, Antony; et al. (Frontiers in Plant Science, 2024)
The epidemic spread of the harmful bacterium Xylella fastidiosa causing the "Olive Quick Decline Syndrome", decimating olive trees in southern Italy, in the region of Apulia, prompted investigations to search for olive genotypes harbouring traits of resistance. A prospecting survey was carried out to identify, in the heavily infected area of Apulia, olive genotypes bearing resistance. Given the limited genetic diversity in the commercial olive groves with few cultivars widely cultivated, surveys targeted predominantly spontaneous olive genotypes in natural and uncultivated areas. Trees, selected for the absence of symptoms, were subjected to diagnostic tests and parentage analysis to disclose their genetic background. Transcriptomic analyses were also employed to decipher the molecular pathways in resistant genotypes. Artificial inoculations were carried out to confirm the resistant phenotype of four open-pollinated seedling of the cultivar Leccino. Among the 171 olive collected genotypes, 139 had a unique SSR profiles, with the cultivar Leccino, Cellina di Nardò and Ogliarola salentina being the most frequent candidate parents. Among the Leccino progeny (n. 61), 67% showed either a highly resistant (HR), resistant (R) or tolerant (T) phenotype to infection by Xylella fastidiosa. The occurrence of such phenotypes among those deriving from Cellina di Nardò and Ogliarola salentina was 32% and 49% respectively. Analyses of the transcriptomic profiles of three Leccino bearing genotypes, naturally infected and not showing symptoms, unravelled that a total of 17,227, 13,031, and 4,513 genes were found altered in the expression, including genes involved in photosynthesis, cell wall or primary and secondary metabolism. Indeed, transcriptome analyses showed that one of these genotypes (S105) was more resilient to changes induced by the natural bacterial infection than the remaining two (S215 and S234). This study consolidates the evidence on the presence and heritage of resistance traits associated with the cv Leccino. Moreover, valuable insights were gathered when analyzing their transcriptomic profiles, i.e. genes involved in mechanisms of response to the bacterium, which can be used in functional genetics approaches to introduce resistance in susceptible cultivars and initiate strategies in olive breeding programs through Marker Assisted Selection